BOOK REVIEW Brand Singapore: Nation Branding in a World Disrupted by Covid-19 (3rd Edition) - Daengrasmisopon, Thittapong (ASEAN Journal of Management & Innovation, 2023)
Brand Singapore: Nation Branding in a World Disrupted by Covid-19 is a success story written by Koh Buck Song in which he describes how the small island country of Singapore can use nation branding strategies to develop itself into the world renowned Lion City. Following the first two editions, namely Brand Singapore: How Nation Branding Built Asia’s Leading Global City (Koh, 2011) and Brand Singapore: Nation Branding after Lee Kuan Yew, in a Divisive World (Koh, 2017), this third edition continues the previous classic brand story by providing additional viewpoints on how the nation might look into refreshing its brand direction after the Covid-19 pandemic amid the rise of social media. The author is a Singaporean brand advisor, author, and editor who has been involved with the nation branding of Singapore for many years. There are seven chapters plus an introduction, endnotes, an index and a section about the author. Each chapter provides an in-depth analysis of the real-world case study of Singapore in various aspects of its brand-building strategy.